(3cJGH aj Gdabg GdMfais ((3SYO Hf eMeO Hf YeQ s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje QH Jee HGdNjQ GdbSe GdKGfi ai cJGH CMcGe GdWdGb heG jJCcO Hg GdegQ heG jSbW Hg HGH GdeWdbI GdKdGK eJi JMd s
(3BNQgG (B:s
(3HGH GdMda Ydi GdTQH hdh bGd Pdc defchMJg jJUQa Edi GdeQGLYI HGdbhd dCf GdbUO YdjgG dG jJUhQ hGddg CYde Je GdeLdO GdKGdK HMeO Gddg hMSf Jhajbg jJdhg cJGH GdMOhO s
(3GdfSNI HgG MhGTs
(3jJVef GdWdGb heSGFdgs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3Gdabg GdMfajs